The smart girl's guide to privacy : practical tips for staying safe online - Blue, Violet (No Starch Press, 2015)
"Discusses how to protect personal information from online privacy violations. Covers how to set and store secure passwords, monitor online visibility, safely use social media and apps, and create online profiles. Contains emergency instructions for those who have been hacked or had their identity, phone, or laptop stolen"--